TWO CULTURES: DIFFERENT ASPECTS OF THE UZBEK-ENGLISH WEDDING CEREMONY - Sotvoldieva , Mokhinur (Innovative Development in Educational Activities, 2023)
In this scientific work, the similarities and differences of the national-cultural traditions of the Uzbek-English wedding ceremonies related to marriage will be discussed.